Current Clinical Brain Tumor Imaging. Issue 3 (September 2017) - Villanueva‐Meyer, Javier E.; Mabray, Marc C.; Cha, Soonmee
Abstract : N/A: Neuroimaging plays an ever evolving role in the diagnosis, treatment planning, and post‐therapy assessment of brain tumors. This review provides an overview of current magnetic resonance imaging (MRI) methods routinely employed in the care of the brain tumor patient. Specifically, we focus on advanced techniques including diffusion, perfusion, spectroscopy, tractography, and functional MRI as they pertain to noninvasive characterization of brain tumors and pretreatment evaluation. The utility of both structural and physiological MRI in the post‐therapeutic brain evaluation is also reviewed with special attention to the challenges presented by pseudoprogression and pseudoresponse.